2021
DOI: 10.2166/wh.2021.140
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of hand-hygiene practices in India: reflections from the 76th round National Sample Survey, 2018

Abstract: This paper studies the differences and determinants of handwashing practices in India and identifies sections of the population with poor handwashing practices who are relatively more vulnerable during the COVID-19 pandemic. We have used the data from the recent National Sample Survey (NSS, 76th round) for India (2018). Bivariate and logistic regression analyses have been performed to predict the determinants of handwashing practices across states and socio-economic groups. Levels of education of the household… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…A total of 1,15,285 samples were studied in the meta-analysis. Of these, the study by Gupta and Anand 29 had the smallest number of samples (N = 106) and the largest number in the study by Biswas and Karmakar 30 (N = 1,06,837). Among the studies sought for meta-analysis, three studies were conducted before the COVID-19 pandemic 27 , 31 , 32 and two studies after the outbreak 29 , 30 .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…A total of 1,15,285 samples were studied in the meta-analysis. Of these, the study by Gupta and Anand 29 had the smallest number of samples (N = 106) and the largest number in the study by Biswas and Karmakar 30 (N = 1,06,837). Among the studies sought for meta-analysis, three studies were conducted before the COVID-19 pandemic 27 , 31 , 32 and two studies after the outbreak 29 , 30 .…”
Section: Resultsmentioning
confidence: 97%
“…Three studies 7 , 25 , 30 identified that education level is a determinant of HH practice. The households with high education levels for the head of the house reported a better rate of HH practices than those with lower education levels.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Handwashing is a simple and effective hygiene measure. Biswas & Karmakar (2022) analysed data from a recent National Sample Survey for India to assess trends in handwashing across the country. They considered a very broad range of factors including caste, class, monthly expenditure, religion, together with water and sanitation access criteria.…”
Section: Household Water Use and Compliance With Public Health Advicementioning
confidence: 99%